Faktor Pendukung Penyajian Kembali Laporan Keuangan - Elfina Sambuaga; Chelsea Chen; Kristina Fransiska; Jeanette Yovanka (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study is to empirically scrutinize the effects of audit quality, audit report lag, and audit committee characteristic towards the length of financial restatements. The population analyzed in this study involves companies listed in Indonesia Stock Exchange during 2016 to 2018. Purposive sampling technique is employed in this research, which results to the total of 153 observations. Multiple regression analysis identifies that audit quality, audit report lag, and audit committee characteristic as statistically significant in explaining the length of financial restatements. Audit committee characteristic and audit report lag compress the length of financial restatements, while audit quality extends the length of financial restatements.